Herpetofauna de la Estación Forestal Experimental Zoquiapan (EFEZ), México: Análisis de su diversidad en tres hábitats distintos - Pérez-Roblero, Claudia Yaniris; Sánchez-Trejo, Rubén; Corcuera, Pablo; Zavala-Hurtado, José Alejandro; Zárate-Hernández, Rocío (Instituto de Ecología, A.C., 2019)
We analyzed the diversity patterns of amphibians and reptiles in three different habitats of a temperate environment: Pine, Pine-Alder and Pine-Fir of the Estación Forestal Experimental Zoquiapan (EFEZ), in the protected natural area Parque Nacional Iztaccíhuatl-Popocatépetl-Zoquiapan. Systematic samplings of the herpetofauna were carried out in belt transects of 1,000 m long and 10 m wide, from 2015 (May-July and September-November) to 2016 (January-March). A total of 4,762 individuals were recorded corresponding to seven families, ten genera and 15 species (five amphibians and ten reptiles). The families with more species and abundance were Phrynosomatidae and Pletodontidae. Species richness was greater (15 species) in the Pine-Alder habitat, whereas abundance was significantly higher ( = 70.18 ind./ha) in the Pine habitat. The Pine-Fir habitat exhibited the lowest richness (13 species) and abundance ( = 36.66 ind./ha). The highest diversity (1D = 5.16) was recorded in Pine-Alder, followed by Pine-Fir (1D = 4.01) and Pine (1D = 3.84). Species’ abundance distribution fitted the Fisher logarithmic series. The most common species in all three habitats were Sceloporus grammicus and Pseudoeurycea leprosa, while all snakes were considered rare species. The 86.7% of the species are endemic to Mexico, of which the 69.2% are endemic to the Trans-Mexican Volcanic Belt. The 33.3% of the species are threatened and 26.7% are under special protection in the NOM-059-2010. Four of these are categorized by the IUCN, of which the 6.7% is endangered, 13.3% is vulnerable and 6.7% is near threatened. In terms of the species-area relationship, amphibians and reptiles’ species richness, as well as the occurrence of endemism in the EFEZ are high. This study contributes to the knowledge on the richness, abundance, distribution and diversity of amphibians and reptiles of the temperate habitats of the station, which would lay the basis to the development of strategies for the conservation of herpetofauna biodiversity.